2003
DOI: 10.1002/anie.200390115
|View full text |Cite
|
Sign up to set email alerts
|

Salinosporamide A: A Highly Cytotoxic Proteasome Inhibitor from a Novel Microbial Source, a Marine Bacterium of the New Genus Salinospora

Abstract: We recently reported the cultivation and phylogenetic characterization of a new group of obligate marine actinomycete bacteria that is widely distributed in ocean sediments.[1] Analogous soil-derived actinomycetes have been the single most significant source of naturally occurring microbial antibiotics, [2] thus the discovery of a major new group of these bacteria in marine sediments suggests that the ocean represents an overlooked habitat from which to isolate these important microorganisms. Given that the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
316
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 955 publications
(346 citation statements)
references
References 10 publications
7
316
0
7
Order By: Relevance
“…Initial screening of NPI-0052 against the NCI panel of 60 tumour cell lines showed GI 50 of o10 nM in all cases (Feling et al, 2003). In concert with these observations, our data showed that (1) NPI-0052 induces apoptosis in MM cells sensitive and resistant to conventional and Bortezomib therapies; and (2) IC50 of NPI-0052 for MM cells is within the low nanomolar concentration (Chauhan et al, 2005a).…”
Section: In Vitro and In Vivo Antitumour Activity Of Npi-0052supporting
confidence: 72%
See 2 more Smart Citations
“…Initial screening of NPI-0052 against the NCI panel of 60 tumour cell lines showed GI 50 of o10 nM in all cases (Feling et al, 2003). In concert with these observations, our data showed that (1) NPI-0052 induces apoptosis in MM cells sensitive and resistant to conventional and Bortezomib therapies; and (2) IC50 of NPI-0052 for MM cells is within the low nanomolar concentration (Chauhan et al, 2005a).…”
Section: In Vitro and In Vivo Antitumour Activity Of Npi-0052supporting
confidence: 72%
“…Specifically, delineation of mechanisms mediating interaction of proteasome inhibitors with 20S proteasome will allow designing potent and therapeutically efficacious proteasome inhibitors. In this context, our recent study characterised a novel proteasome inhibitor NPI-0052, a small molecule derived from fermentation of Salinospora, a new marine Gram-positive actinomycete (Feling et al, 2003;Macherla et al, 2005;Chauhan et al, 2005a). Importantly, NPI-0052 is distinct from Bortezomib, orally bioactive, and an equipotent antitumour agent (Chauhan et al, 2005a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6]; salinosporamide-A, an anticancer metabolite (Salinispora sp.) [7]; marinomycins (Marinophilus sp.) [8]; abyssomicin-C (Verrucosispora sp.)…”
Section: Introductionmentioning
confidence: 99%
“…Enrichments or isolates facilitate better assessment of the physiology, structure, and function of populations within a complex microbial community. In fact, the study of enrichments and isolates has resulted in discoveries as diverse as determining the enzymes responsible for degradation of the pollutant vinyl chloride (4), isolating possible anticancer agents (5), and understanding the cell structures of bacteria within candidate phyla with no cultured representatives (6). Unfortunately, while culturing techniques have improved, they still rely heavily on knowledge of an organism's ideal growth conditions and tend to enrich the fastest growing organisms in a sample (7).…”
mentioning
confidence: 99%